Characterization of Paramagnetic Reactive Intermediates: Predicting the NMR Spectra of Iron(IV)–Oxo Complexes by DFT. Issue 37 (28th July 2015) - Borgogno, Andrea; Rastrelli, Federico; Bagno, Alessandro
Abstract The relative energies of spin states of several iron(IV)–oxo complexes and related species have been calculated with DFT methods by employing the B3LYP* functional. We show that such calculations can predict the correct ground spin state of FeIV complexes and can then be used to determine the 1H NMR spectra of all spin states; the spectral features are remarkably different, hence calculated paramagnetic 1H NMR spectra can be used to support the structure elucidation of numerous paramagnetic complexes. Applications to a number of stable and reactive iron(IV)–oxo species are described.